2017
DOI: 10.1097/mej.0000000000000294
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pediatric basic life support self-led and instructor-led training among nurses

Abstract: Self-training is not statistically different to instructor-led training in teaching PBLS. Self-evaluated confidence improved, but showed no difference between groups. PBLS may be disseminated through self-training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
1
11
0
2
Order By: Relevance
“…Some healthcare professionals consider it too elaborate and rigid, while others think it misses important clinical information (unpublished data). The approach also lacks a firm evidence base in terms of effectiveness and benefit for patient outcomes [12]. On the other hand, a structured approach, such as the ABCDE algorithm, helps healthcare professionals to focus on the most life-threatening problems and guides initial treatment choices [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some healthcare professionals consider it too elaborate and rigid, while others think it misses important clinical information (unpublished data). The approach also lacks a firm evidence base in terms of effectiveness and benefit for patient outcomes [12]. On the other hand, a structured approach, such as the ABCDE algorithm, helps healthcare professionals to focus on the most life-threatening problems and guides initial treatment choices [12].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found promising results for VBI, including improved practical skills and increased self-confidence [7][8][9][10]. However, the majority of these studies used an instructional video as part of a self-directed learning approach instead of an in-hospital course [11,12]. Furthermore, evidence regarding the most effective instruction method for teaching the ABCDE approach in particular is virtually absent.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the e-learning method produced better results in chest compression depth and in the volume of ventilation [30]. A study by Vestergard et al assessed the effectiveness of an e-learning course versus a traditional instructor-led pediatric BLS course administered to a group of nurses, and reported no statistically significant differences in the results produced by the 2 methods [23].…”
Section: Discussionmentioning
confidence: 99%
“…Quality of CPR is inseparably linked with regularly-held training and the instruction method provided to medical personnel. In addition to the conventional manikin-based practical training supervised by instructors, alternative approaches, which are more and more frequently being investigated by researchers, make use of feedback devices [5,15,16], BLS video self-instruction systems [1722], e-learning [6,23], and real-time audio-visual feedback systems [24,25]; these methods carry a promise for accessible, affordable, and time-effective training in resuscitation [26].…”
Section: Introductionmentioning
confidence: 99%
“…Instructor-led training is one of the most common forms of employee training. It takes the form of a classroom setting where the trainer (instructor) passes knowledge to the trainees (employees) through presentations (Vestergaard, Løfgren, Jessen, Petersen, Wolff, Nielsen & Krarup, 2017). Instructor-led training is usually interactive.…”
Section: Instructor-led Trainingmentioning
confidence: 99%